Non-linear static analysis of steel Framed Structures (Journal of Civil Engineering Researchers, 2017)
This paper aims to evaluate the zone Ⅱ.selected steel framed building to conduct the non-linear static analysis (Pushover Analysis). The pushover analysis shows the pushover curves, capacity spectrum, plastic hinges and performance level of the existing building. The non-linear static analysis gives better understanding and more accurate seismic performance of buildings as progression of damage or failure can be traced.The proposed building is the regular shaped three-storeyed steel structure.Its height is 9.8m above the ground level. The structure is composed of steel moment resisting frame and it is designed out by SAP-2000 Version 18 software. There are 204 hinges in the building to present the capacity curve and performance level. And also, it can get the knowledge of FEMA_356 usage in pushover analysis.
Keywords: Seismic zone; Pushover Analysis; capacity spectrum; FEMA_356; SAP-2000